Catastrophic Health Expenditure: An Experience from Health Insurance Program in Nepal - Paudel, Deepak Raj (Emerging Science Journal, 2019)
High expenditure due to health care is a noted public health concern in Nepal and such expenditure is expected to reduce through the access to health insurance. This study determines the factors affecting householdâ€™s catastrophic health care expenditure in Kailali district, where the government health insurance program was first piloted in Nepal. A cross-sectional survey was conducted from January to February 2018 among 1048 households (6480 individuals) after 21 months of the execution of the social health insurance program. Â For the sample selection, wards were selected in the first stage followed by the selection of the households. Overall, 17.8% of the households reported catastrophic health expenditure using a threshold of more than 10% of out-of-pocket payment to total household expenditure. The study found that households without having health insurance, low economic status, and head with low level of education were more likely to face catastrophic spending. The findings suggest a policy guideline in the ongoing national health insurance debate in Nepal. The government health insurance program is currently at expansion stage, so, increase in insurance coverage, could financially help vulnerable households by reducing catastrophic health expenditure.